Post-operative hemimaxillectomy rehabilitation using prostheses supported by zygoma implants and remaining natural teeth (Clinics, 2016)
OBJECTIVES: This study aimed to evaluate the stability of prostheses supported by zygoma implants and remaining teeth for subjects who had undergone hemi-maxillectomy. METHODS: Ten patients were included in the study. Oral rehabilitation was performed using a temporary prosthesis that was supported by remaining teeth for the first three months. Then, a zygoma implant was placed to provide support for a final prosthesis in addition to the remaining teeth. Each prosthesis was tailor-made according to biomechanical three-dimensional finite element analysis results. The patients were assessed using the prosthesis functioning scale of the Memorial Sloan-Kettering Cancer Center. In addition, retention and bite force were recorded for both the temporary prosthesis and the final prosthesis. RESULTS: The mean bite force of the prosthetic first molar was increased to 69.2 N. The mean retentive force increased to 13.5 N after zygoma implant insertion. The bite force on the prosthetic first molar was improved to 229.3 N. CONCLUSION: Bite force increased significantly with the support of a zygoma implant. The use of zygoma implants in the restoration of maxillary defects improved functional outcome and patient satisfaction.